Legal regulation of the internal migration process in the Republic of Kazakhstan - Amerkhanova, И.К.; Jussibaliyeva, А.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
Migration is one of the most acute problems of the modern world. As in all countries, the process of internal migration requires constant regulation in Kazakhstan. Improving the legal regulation of internal migration is one of the main tasks of the state migration policy in Kazakhstan. The study of the migration process is based on uniform principles, i.e. on the factors that determine internal, external, legal, and illegal migration flows. The article analyzes the main regulations that reflect the principles and priorities of state regulation of internal migration in the Republic of Kazakhstan. Kazakhstan needs a unified scientifically substantiated, balanced, and understandable state route of internal migration. In Kazakhstan, there is voluntary resettlement of people from densely populated areas to labor-deficient ones. Therefore, a comprehensive study of the process of internal migration is the main task of jurisprudence.